(3TQM Gdcde GdfHhjI aj GdMce GdWHjIs - (3CMeO Hf SYjO Hf MdhGf GdWHjH GHf GdYGdeI,J (B652 (3g` s
(3ChdgG (B:s
(3CMeOc jG bjhe aEf ai GdCMGOjK GdfHhjI ef GdMce GdWHjI eG jYeb Ydi GdaWf bQGQg , hJHYO Yf GdbQGFM ObGFb Yedg hYdeg s
(3BNQgG (B:s
(3JcdeJ ai gPG HMSH eG CYWGfi Gddg JYGdi ef GdEOQGc hhgHfi ef GdYbd ,hcd TF HbOQ SGHb , hGdYde Ydi GdMbjbI ddg YR hLd s
(3fSNI ddNRGfI GdehdhjI GdUGMHjI GdhRjQjI GdLeGdjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B133 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B_(3GdRGhjI GdMeRGhjI (B(135) s
Keywords: (3GdWHs